1988
DOI: 10.1302/0301-620x.70b3.3372555
|View full text |Cite
|
Sign up to set email alerts
|

Low friction arthroplasty for old quiescent infection of the hip

Abstract: We report the results oflow friction arthroplasty in 72 old tuberculous hips and 42 hips with old quiescent septic arthritis. Follow-up was for a minimum oftwo years. Recrudescence oftuberculosis was seen in only one patient, but deep infection occurred in four of the hips with previous septic arthritis. The reasons for this are discussed. It is recommended that patients with old tuberculous hips should have a course of anti-tuberculous drugs before operation, that patients with previous septic infection shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
5

Year Published

1993
1993
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 0 publications
2
19
0
5
Order By: Relevance
“…The two issues that need to be addressed are control of the infection and treatment of the degenerative joint. Although arthroplasty is needed for the treatment of the degenerative joint, an existing infection is a contraindication to joint arthroplasty [1,7,8,11,13,14] because it will likely lead to a periprosthetic joint infection [1,13,22]. It is well documented that two-stage exchange arthroplasty with the use of an articulating antibiotic spacer not only controls infection, but improves pain and function in a periprosthetic joint infection [9,12,15,23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The two issues that need to be addressed are control of the infection and treatment of the degenerative joint. Although arthroplasty is needed for the treatment of the degenerative joint, an existing infection is a contraindication to joint arthroplasty [1,7,8,11,13,14] because it will likely lead to a periprosthetic joint infection [1,13,22]. It is well documented that two-stage exchange arthroplasty with the use of an articulating antibiotic spacer not only controls infection, but improves pain and function in a periprosthetic joint infection [9,12,15,23].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies [7,10,13,14,22] have reported the use of THA in patients with quiescent childhood infections with periprosthetic infection rates ranging from 0% to 12.5% with higher infection rates in those patients with active infection less than 10 years from the time of their THA. Jupiter et al [11] evaluated patients with current or quiescent infection treated with THA and found a 22% periprosthetic infection rate in those with current infection and a 4% periprosthetic infection rate in those treated with quiescent infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] font 6tat de 13 cas qui correspondent tous ~ des arthrites septiques de l'enfance ass~ch6es depuis de nombreuses ann6es. I1 semble en ~tre de marne dans le travail plus r6cent de Laforgia [8].…”
Section: Discussionunclassified
“…There have been few reports on tuberculosis as a cause of late infection of a total hip arthroplasty [5,19,16,17,18,20,21]. McCullough described a case in whom the tuberculous infection was presumed to be a reactivation of calcified mesenteric lymph nodes [221.…”
Section: Introductionmentioning
confidence: 99%